Effects of canopy composition and disturbance type on understorey plant assembly in boreal forests. (14th July 2015) - Fourrier, Arnaud; Bouchard, Mathieu; Pothier, David; Collins, Beverly
Abstract Questions What are the relative roles of disturbance type and canopy composition on understorey plant assemblages? Are these two environmental filters of equal importance in driving understorey patterns? Does a trait‐based approach improve understanding of plant assemblage responses in disturbed boreal forests? Location Eastern boreal forests of North America, Québec, Canada. Methods We sampled understorey plant assemblages in ca. 30‐yr‐old forest stands originating from three types of disturbance (clear‐cutting, fire and spruce budworm outbreak) and two dominant canopy compositions (coniferous and deciduous). For each disturbance × canopy combination, at least eight stands were sampled. The results were analysed with a combination of multivariate (RDA, PERMANOVA), univariate (IndVal) and trait‐based (fourth‐corner) approaches. Results Overall, canopy composition was a more important driver than disturbance type for understorey plant communities. Species richness and particularly the abundance of herbaceous species were highest under deciduous canopies, whereas bryophytes and lichens were more diverse and abundant under coniferous canopies. Light‐demanding species with abundant seed production were mostly restricted to deciduous canopies. Some patterns were also explained by disturbance type, but these were mostly associated with the presence/absence of non‐abundant species or species groups such as lichens. Conclusions We propose that the higher effect of canopy composition compared with disturbance type can be explained by two factors. First, the effect of canopy composition tends to remain present for decades during stand development, whereas the effect of the disturbance type tends to dissipate progressively after the stand‐initiating disturbance. Second, in boreal forests, most understorey plant species possess reproduction strategies (such as vegetative reproduction) that make them well adapted to persist in stands affected by any type of disturbance. At the landscape level, maintaining the right proportion of deciduous and coniferous stands through forest management could ensure that understorey ecosystem processes and plant diversity are maintained. However, creating or maintaining specific post‐disturbance attributes could be important for the conservation of species affiliated with specific substrates.